2017
DOI: 10.3892/br.2017.895
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of inflammation by the rhizome of Anemarrhena asphodeloides via regulation of nuclear factor-κB and p38 signal transduction pathways in macrophages

Abstract: Abstract. The rhizome of Anemarrhena asphodeloides Bunge (A. asphodeloides) has been used as a traditional East Asian medicine for the treatment of various types of inflammatory disease. However, to the best of our knowledge, there have been no systemic studies regarding the molecular mechanisms of action of the A. asphodeloides rhizome anti-inflammatory effects. The aim of the present study was to elucidate the anti-inflammatory effects and underlying mechanism of action of ethanol extracts of the rhizome of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…In addition, previous research thought the anti-inflammatory effects of ZDW come from its antioxidant properties of five components: Fu Ling ( Poria cocos ), Zhi Mu ( Rhizoma Anemarrhenae ), Shu Di Huang ( Radix Rehmanniae Preparata ), Shan Zhu Yu ( Fructus Corni ), and Huang Bai ( Cortex Phellodendri ) [ 20 24 ]. For example, Fu Ling extract regulates the inflammatory response of macrophages via inhibition of iNOS, COX-2, IL-1 β , and TNF- α through inactivation of the NF- κ B signaling pathway [ 24 26 ]; the aqueous extract of Zhi Mu and Shan Zhu Yu was reported to exert it has anti-inflammatory and analgesic effects by suppressing COX-2 and iNOS expression through the downregulation of NF-kappaB binding activity [ 27 31 ]. In addition, many animal studies reported that Fu Ling possesses protective effects against chemical-induced liver injuries [ 32 , 33 ]; Shan Zhu Yu can be used to treat diabetic or epileptic rats through the regulation of their immune function [ 28 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, previous research thought the anti-inflammatory effects of ZDW come from its antioxidant properties of five components: Fu Ling ( Poria cocos ), Zhi Mu ( Rhizoma Anemarrhenae ), Shu Di Huang ( Radix Rehmanniae Preparata ), Shan Zhu Yu ( Fructus Corni ), and Huang Bai ( Cortex Phellodendri ) [ 20 24 ]. For example, Fu Ling extract regulates the inflammatory response of macrophages via inhibition of iNOS, COX-2, IL-1 β , and TNF- α through inactivation of the NF- κ B signaling pathway [ 24 26 ]; the aqueous extract of Zhi Mu and Shan Zhu Yu was reported to exert it has anti-inflammatory and analgesic effects by suppressing COX-2 and iNOS expression through the downregulation of NF-kappaB binding activity [ 27 31 ]. In addition, many animal studies reported that Fu Ling possesses protective effects against chemical-induced liver injuries [ 32 , 33 ]; Shan Zhu Yu can be used to treat diabetic or epileptic rats through the regulation of their immune function [ 28 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Korea, A. asphodeloides B is employed as antipyretic, diuretic, sedative, and antitussive medicine ( Lee et al, 2018 ). The study of ethanol extracts of A. asphodeloides B revealed anti-osteoporotic effects, inhibiting osteoclastogenesis and reducing inflammation ( Kim et al, 2017 ). Dichloromethane fractions of A. asphodeloides B showed EA with a RP of 1.9 × 10 –4 (RP of Estradiol (E2) was 1.0) ( Kim et al, 2008 ).…”
Section: Estrogenic Plants For Menopausementioning
confidence: 99%
“…Calculated gene expression was normalized to reference genes, glyceraldehyde 3-phosphate dehydrogenase (GAPDH) and β-actin. The sequences of the PCR primers are listed in a previous study (41).…”
Section: Methodsmentioning
confidence: 99%